Diagnosis, Tatalaksana, Pencegahan, dan Diagnosis Defensial Depresi Pasca Stroke - Ilhamsyah Putra Sinaga; Evi Kurniawati (CV. Jasa Sukses Abadi, 2021)
Post-Stroke Depression (PSD) is a common psychiatric symptom after stroke. PSD is a condition in which stroke patientsexperience traumatic events that damage their physical and mental integrity, autonomy and self-esteem, and social values.Lack of psychological coping mechanisms, as well as premorbid personality, are determinants of PSD. PSD patients mostlypresent with fluctuation in mood, retardation, irritability, or apathy. PSD is a major factor that can inhibit the recovery ofneurological function and daily activities in stroke patients, and is associated with increased mortality. A recent meta-analysisshowedthattheprevalenceofPost-StrokeDepression(PSD)was29%.PSDdealswiththedisruptionofmonoamine circuits either directly or indirectly. In cytokine theory, inflammation of PSD may be related to the production of“depressogenic” cytokines by the inflammatory response to ischemia. This may be related given that inflammatorycytokines, such as IL-1, IL-6, IL-18, and tumor necrosis factor (TNF) -alpha increase significantly after stroke. Biological andpsychological conditions cause PSD either due to lesions, biogenic amines, inflammatory cytokines, or geneticpolymorphisms. PSD must be distinguishable from post-stroke apathy, post-stroke anxiety (PSA), post-stroke fatigue (PSF),and post-stroke psychotic disorder (PSPD). The goal of PSD treatment is to achieve complete remission of the symptoms ofa depressive episode, which may have a beneficial impact on the recovery of neurological deficits. Management can bedone with pharmacological and non-pharmacological interventions in the form of neuromodulation and psychosocial. TheThe purpose of this article is to provide information regarding the Post-Stroke Depression (PSD).